2009
DOI: 10.1373/clinchem.2008.110395
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies against Synthetic Deamidated Gliadin Peptides for Celiac Disease Diagnosis and Follow-Up in Children

Abstract: The best available index for diagnosing CD in children was tTG IgA. In infants <2 years old, AGA IgG II performed as well as tTG IgA in cases without total IgA deficiency and allowed detection of CD when total IgA was <0.06 g/L. Gluten-free diet monitoring can be achieved using any of the studied serum markers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

17
75
1
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(94 citation statements)
references
References 40 publications
17
75
1
1
Order By: Relevance
“…The high diagnostic sensitivity obtained with the IgG-anti-dGli assay is comparable with results of previous smaller studies on IgA-deficient CD patients (9,19 ) and with reports on individual IgA-deficient cases (17,18 ) applying another test based on dGli as the antigen.…”
supporting
confidence: 87%
See 1 more Smart Citation
“…The high diagnostic sensitivity obtained with the IgG-anti-dGli assay is comparable with results of previous smaller studies on IgA-deficient CD patients (9,19 ) and with reports on individual IgA-deficient cases (17,18 ) applying another test based on dGli as the antigen.…”
supporting
confidence: 87%
“…Recently, 8 IgA-deficient CD children were described (11,17,18 ) who all had low concentrations of IgA-anti-tTG and IgA-anti-dGli but high concentrations of IgG-anti-dGli. Two further studies, each including 20 IgA-deficient CD patients, revealed higher accuracy of IgG-anti-dGli detection compared with antibodies against native gliadin (9,19 ).…”
mentioning
confidence: 99%
“…The DGP concentrations declined and became negative more rapidly than the tTG concentrations. This difference in Ab kinetics has been described earlier (2,8).…”
supporting
confidence: 73%
“…The anti-DGP antibody test provides a more specific marker for disease compared to its predecessor, the antigliadin antibody assay. Although the anti-DGP antibody test is not currently recommended for routine screening, it may be useful for patients in whom suspicion of CD is high, but anti-tTG and/or EMA is not detected (39,40).…”
Section: Celiac Disease Serologic Tests and Recommendations For Screementioning
confidence: 99%
“…Early clinical studies suggested that EMA and AGA tests are useful in very young children (Table 1); however, more-recent data indicate that anti-tTG or DGP IgA immunoassay is similar and in some cases more accurate than the AGA immunoassay (29, c The positive predictive value (PPV) and negative predictive value (NPV) both had a pretest probability of 5%. 30,39,40,42,43). In one of the most recent studies examining the significance of AGA, EMA, and ARA in genetically at risk children for CD from birth, AGA IgG appeared Ն3 months earlier than anti-tTG, with anti-tTG, EMA, and ARA emerging concurrently (44).…”
Section: Testing For Antireticulin Antibodies Is Obsolete In the Evalmentioning
confidence: 99%